How to become a better reader - Witty, Paul, 1898-1976 (Science Research Associates, 1953)
This book is designed to help you become a better reader. If you are an average reader, you may be reading this book now at a reading rate of about 180 words per minute. You can improve your rate of reading -- perhaps 50 percent or more for many types of reading. At the same time, you can learn to get more out of the things you read. - p. 1.